Perfect anomalous refraction metasurfaces empowered half-space optical beam scanning - Tao He; Dongdong Li; Chengfeng Li; Haigang Liang; Chao Feng; Jingyuan Zhu; Lingyun Xie; Siyu Dong; Yuzhi Shi; Xiong Dun; Zeyong Wei; Zhanshan Wang; et al. (Nature Communications)
Abstract Metasurface-based optical beam scanning devices are gaining attention in optics and photonics for their potential to revolutionize light detection and ranging systems. However, achieving anomalous refraction with perfect efficiency (>99%) remains challenging, limiting the efficiency and field of view (FOV) of metasurface-based optical beam scanning devices. Here, we introduce a paradigm for achieving perfect anomalous refraction by augmenting longitudinal degrees of freedom arousing a multiple scattering process to optimize symmetry breaking. An all-dielectric quasi-three-dimensional subwavelength structure (Q3D-SWS), composed of a purposely designed multilayer film and a dielectric metasurface separated by a spacer, is proposed to eliminate reflection loss and spurious diffraction, achieving >99% anomalous refraction efficiency. By independently rotating two cascaded Q3D-SWSs, we experimentally showcase half-space optical beam scanning, achieving a FOV of 144° × 144°, with a maximum efficiency exceeding 86%. Our results open new avenues for high-efficiency metasurfaces and advances applications in light detection and ranging systems.